Strategi Humas Sudin Kominfomas Kota Administrasi Jakarta Timur Melalui Kegiatan Gelar Budaya Betawi Dan Budaya Nusantara - Leliana, Intan; Sita Muliawati; Endah Supriyatna (LPPM Universitas Bina Sarana Informatika, 2020)
The role of public relations is very important in shaping the image of the government, without good public relations its performance will not be seen by the public even though the government apparatus has worked as well as possible. On the other hand, an effective public relations approach can cover the lack of government performance. The purpose of this study is to take a deeper look at how the archipelago culture degree program is carried out by the Public Relations of the East Jakarta Kominfomas Sub-dept. The method used in this research is to use a descriptive qualitative approach by describing the situation as it is based on the activities that take place in the field. The results of this study show that this activity plays an active role in introducing Betawi culture and archipelago culture, so that culture as a national identity can be loved by the younger generation and has a selling value in foreign eyes that is no less cool than foreign culture. Keyword: Public Relations Strategy, Betawi Culture Degree